If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+3)x6=48
We move all terms to the left:
(x+3)x6-(48)=0
We multiply parentheses
x^7+3x^6-48=0
We do not support expression: x^7
| 2v^2–9v+8=0 | | 2v^2+6v+9=0 | | 6y-33=3(4y-5) | | 3b=9-8b=11 | | 8u^2+4u+5=0 | | 2x2+x-51=0 | | 4a^2/3-16=0 | | -5(2b+4)=28-8b | | 0.333x=15 | | 0.25x-8=8 | | 0.50x=4 | | -(2X-7)=31-10x | | 0.3w=0.8-0.2w | | 5/9f+36=117 | | 7-4(3b-3)+4b=15 | | d/4+8=16 | | x-1.75=-1.75 | | 4x-7+x-8X=-1 | | 4n-(6n-1)=1+n | | 28=14x+42 | | 6m-m=6(6m-10) | | 7=22-3b | | 2/12-2x/4=4x/6+2/8 | | 6m-m=5—6(6m-10) | | 5x+9-3x=15-x | | x/2-5=4x/4-8 | | 2/5x=x+24/5 | | 5=2*x-1 | | 60=4-8x | | -7−9g=8g−7 | | -7+2x=-8 | | 10z+8=8z |